Phenotypic characterization of genetically lowered human lipoprotein(a) levels - Emdin, C; Khera, A; Natarajan, P; Klarin, D; Won, H; Peloso, G; Stitziel, N; Nomura, A; Zekavat, S; Bick, A; Gupta, N; Asselta, R; et al. (Elsevier, 2016)
BACKGROUND: Genomic analyses have suggested that the LPA gene and its associated plasma biomarker, lipoprotein(a) (Lp[a]), represent a causal risk factor for coronary heart disease (CHD). As such, lowering Lp(a) levels has emerged as a therapeutic strategy. Beyond target identification, human genetics may contribute to the development of new therapies by defining the full spectrum of beneficial and adverse consequences and by developing a dose-response curve of target perturbation. OBJECTIVES: The goal of this study was to establish the full phenotypic impact of LPA gene variation and to estimate a dose-response curve between genetically altered plasma Lp(a) and risk for CHD. METHODS: We leveraged genetic variants at the LPA gene from 3 data sources: individual-level data from 112,338 participants in the U.K. Biobank; summary association results from large-scale genome-wide association studies; and LPA gene sequencing results from case subjects with CHD and control subjects free of CHD. RESULTS: One SD genetically lowered Lp(a) level was associated with a 29% lower risk of CHD (odds ratio [OR]: 0.71; 95% confidence interval [CI]: 0.69 to 0.73), a 31% lower risk of peripheral vascular disease (OR: 0.69; 95% CI: 0.59 to 0.80), a 13% lower risk of stroke (OR: 0.87; 95% CI: 0.79 to 0.96), a 17% lower risk of heart failure (OR: 0.83; 95% CI: 0.73 to 0.94), and a 37% lower risk of aortic stenosis (OR: 0.63; 95% CI: 0.47 to 0.83). We observed no association with 31 other disorders, including type 2 diabetes and cancer. Variants that led to gain of LPA gene function increased the risk for CHD, whereas those that led to loss of gene function reduced the CHD risk. CONCLUSIONS: Beyond CHD, genetically lowered Lp(a) levels are associated with a lower risk of peripheral vascular disease, stroke, heart failure, and aortic stenosis. As such, pharmacological lowering of plasma Lp(a) may influence a range of atherosclerosis-related diseases.